Respuesta :

Answer:

[tex]\frac{p^2-25}{p^2-10p+25}[/tex]

We can factorise the numerator with the difference of squares formula:[tex]x^2-y^2=(x+y)(x-y)[/tex]

-----------------------------

[tex]\frac{p^2-5^2}{p^2-10p+25} =\frac{(p+5)(p-5)}{p^2-10p+25}[/tex]

Now we can factorise the denominator:

[tex]\frac{(p+5)(p-5)}{p^2-10p+25} =\frac{(p+5)(p-5)}{(p-5)^2}[/tex]

[tex]\frac{(p+5)(p-5)}{(p-5)^2} =\frac{(p+5)(p-5)}{(p-5)(p-5)}[/tex]

Cancel out the common factor of (p-5):

[tex]\frac{(p+5)(p-5)}{(p-5)(p-5)} =\frac{(p+5)}{(p-5)}[/tex]